2006
DOI: 10.1021/bp050302a
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Bacteria from Fermentation Broth by Body Feed Filtration: A Solved Problem?

Abstract: The direct capture of bacteria produced in high cell density fermentation by filtration is not possible once the milliliter-scale has been surpassed. Filtration in the presence of a filter aid (body feed filtration) constitutes a putative and scalable alternative, but only if conditions proposed by industry for large-scale filtration processes, namely, flow rates (for aqueous solutions) in the range of 500-1,500 L/(m(2) x h) and a filter aid concentration of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, polymer pretreatment on the membrane surface may be required before filtration to enhance performance by providing additional steric barriers and ensuring the retention of millimetrescale cell debris and proteins. 26,27 Eucalyptus is the predominant planted hardwood species worldwide. 28 As a result of improved genetics and silviculture, 29 it supplies increasing quantities of raw materials for wood pulping.…”
Section: Introductionmentioning
confidence: 99%
“…However, polymer pretreatment on the membrane surface may be required before filtration to enhance performance by providing additional steric barriers and ensuring the retention of millimetrescale cell debris and proteins. 26,27 Eucalyptus is the predominant planted hardwood species worldwide. 28 As a result of improved genetics and silviculture, 29 it supplies increasing quantities of raw materials for wood pulping.…”
Section: Introductionmentioning
confidence: 99%
“…2000 L/(m 2 h)), presumably due to the reduced viscosity of the aqueous solution at 70 °C. In addition it is likely that the alumina‐based hydrogel released by the bentonite during incubation (19) is partially dissolved at the acidic pH and comparatively high NaCl concentration in case of the CNS lysis buffer. This will also reduce the backpressure of the filter cake.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria Capture by Filtration. For capture of the bacteria via filtration, the previously published protocol was used (19). Briefly, the bioreactor cultures were stopped before reaching the maximal biomass values, typically at an OD 600 of ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, the optimal flocculation concentration, addressed either by measurement of a filtration time [22] or that of an aggregate size [23], generally decreases with increasing polymer molecular weight in the 10000 to 100000g/mol range [2]. The aggregation of bacteria mediated by low PEI molecular weights (<2000 g/mol) has been shown to lead to longer filtration times, and the restabilization of bacterial suspensions at high polymer concentrations has not been observed [2,22,24]. It has also been reported that the binding of PEI with LPS leads to the release of associated material from the bacterial cell [25,26], inducing bacterial membrane permeabilization [27].…”
Section: -Introductionmentioning
confidence: 99%